To Switch or Not To Switch: Understanding Social Influence in Online Choices. (September 2014) - Zhu, Haiyi; Huberman, Bernardo A.
The authors designed and ran an experiment to measure social influence in online recommender systems, specifically, how often people's choices are changed by others' recommendations when facing different levels of confirmation and conformity pressures. In this experiment, participants were first asked to provide their preference from pairs of items. They were then asked to make second choices about the same pairs with knowledge of other people's preferences. The results show that other people's opinions significantly sway people's own choices. The influence is stronger when people are required to make their second decision sometime later (22.4%) rather than immediately (14.1%). Moreover, people seem to be most likely to reverse their choices when facing a moderate, as opposed to large, number of opposing opinions. Finally, the time people spend making the first decision significantly predicts whether they will reverse their decisions later on, whereas demographics such as age and gender do not. These results have implications for consumer behavior research as well as online marketing strategies.